Pressures on webs in wound rolls due to winding and contact - Mollamahmutoglu, C.; Ganapathi, S.; Good, J. K. (TECH ASSOC PULP PAPER IND INC, 2014)
Paper, film, and metallic webs have designed surfaces. Process engineers design these surfaces to ensure they will coat or print correctly. In some cases, such as tissue, the manufactured surface is designed to provide softness. After the web is formed, care must be taken to maintain the web surface for the intended use or for subsequent processing. Web surfaces can be damaged by contact pressure, which is due to multiple sources. Tissues can suffer decreased loft and softness as a result of excessive pressure. Winding webs into rolls creates pressure on each web layer that varies with radial location. Almost all high speed winders must employ a nip roller in contact with the outer surface of the winding roll to prevent air entrainment. The nip roller, which may or may not be covered with an elastomer, induces local dynamic pressures where it contacts the winding roll that travel at the surface velocity of the winding roll. After rolls are wound, they can witness additional surface contact pressure. Often rolls are stored on flat surfaces and the dead weight of the roll induces contact pressure. In other cases, the roll may be moved by a clamp truck that employs hydraulic pressure to clamp and lift the wound roll. The objective of this paper is to demonstrate a method by which the total pressure in a web due to winding and to contact can be determined. Wound rolls of newsprint and polyester will be subjected to compression tests to verify the method. Application: This research can be applied to limit the pressure between wound rolls and contact surfaces to avoid damage of the web. Web surface damage and product loss can be mitigated by selecting winding and contact conditions that limit the total pressure witnessed by the web.
Keywords: Materials Science